Key Aspects of the State Policy of the USA Concerning Tutoring as an Industry of Supplementary Educational Services - Kateryna Osadcha (Pedagogical Discourse, 2016)
The article highlights the key aspects of the state policy of the USA concerning tutoring as an industry of supplementary educational services. The terms «educational services» and «supplementary educational services» are defined. Supplementary educational services are referred as free academic assistance in reading, language sciences and mathematics given to students and can be provided out-of-class, during weekends and summer holidays. The demand for tutor services in the USA based on vacancy sites (usajobs.gov, dice.com, careerbuilder.com, monster.com, indeed.com) examination is analysed. It is highlighted that great attention to tutoring services in the country has been paid because of increasing problems of students with low achievements in learning. As a consequence the development of supplementary educational services and tutoring have become one of the leading field of the USA policy. The legal acts of the USA such as Elementary and Secondary Education Act, No Child Left Behind Act, Every Student Succeeds Act and recommendations concerning introduction and implementation of the legal acts for educational agencies of the USA and Ukraine are studied. According to the analysis of scientific papers and mass media messages some results of legal acts introduction to the American society are presented. The author comes to conclusion that the state policy of the USA is directed to the improvement of educational achievements of students and development of variable ways for fulfillment of this purpose, including additional federal funding and control of providing supplementary educational services by tutors. In the USA the tutor support of children and teenagers is carried out with the system of state and private educational establishments of different types. The conducted analysis allows to systematize the experience of standardization of the system of supplementary educational services provided by tutors, that, in turn, can be a basis for the development of the state policy of Ukraine in the field of realization of supplementary educational services provided by tutors.Key words: tutoring, foreign experience, the United States of America, legal acts.